2017
DOI: 10.1371/journal.pntd.0005706
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of available treatments for visceral leishmaniasis in Brazil: A multicenter, randomized, open label trial

Abstract: BackgroundThere is insufficient evidence to support visceral leishmaniasis (VL) treatment recommendations in Brazil and an urgent need to improve current treatments. Drug combinations may be an option.MethodsA multicenter, randomized, open label, controlled trial was conducted in five sites in Brazil to evaluate efficacy and safety of (i) amphotericin B deoxycholate (AmphoB) (1 mg/kg/day for 14 days), (ii) liposomal amphotericin B (LAMB) (3 mg/kg/day for 7 days) and (iii) a combination of LAMB (10 mg/kg single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 22 publications
2
49
0
3
Order By: Relevance
“…In Brazil, the Ministry of Health (MH) recommends the following drugs for VL treatment: N-methylglucamine antimoniate, amphotericin B deoxycholate, and liposomal amphotericin B. N-methylglucamine antimoniate has an efficacy of 83.1-96.9% [4][5][6][7] , and is recommended as the first-line treatment for VL, despite its recognized toxicity 8 . Amphotericin B deoxycholate, which is the second choice for the VL treatment is also highly toxic.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, the Ministry of Health (MH) recommends the following drugs for VL treatment: N-methylglucamine antimoniate, amphotericin B deoxycholate, and liposomal amphotericin B. N-methylglucamine antimoniate has an efficacy of 83.1-96.9% [4][5][6][7] , and is recommended as the first-line treatment for VL, despite its recognized toxicity 8 . Amphotericin B deoxycholate, which is the second choice for the VL treatment is also highly toxic.…”
Section: Introductionmentioning
confidence: 99%
“…Its estimated efficacy ranges from 85.0-90.0% 8,9 . Romero et al 6 conducted a randomized clinical study trial in Brazil and observed high toxicity in patients treated with amphotericin B deoxycholate, which led to the discontinuation of that arm of the study. Liposomal amphotericin B is indicated for patients with severe disease, those presenting comorbidities or immunodeficiencies, pregnant women, and those with renal or cardiac toxicity caused by the first-and second-line VL drugs 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our decision‐making models were constructed with epidemiological parameters with a high level of evidence, since they came from a multicenter, randomised, open‐label trial that assessed the efficacy and safety of the drugs used for the treatment of VL in Brazil . Regarding the costs, the study used data that reflect the Brazilian reality, as they were obtained from a the cost‐of‐illness study of VL care in Brazil, that used data from national official information systems .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, treatment with the drug AMBD was not considered, since, although it is available at SUS, it is only intended for patients who cannot be treated with MA or LAMB [10]. Incidentally, the therapeutic arm evaluating AMBD in the study by Romero et al (2017) was suspended following the recommendation of the data safety monitoring board due to safety issues [10]. Also, the evidence on efficacy and safety of AMDB in Brazil is restricted to one clinical trial comparing AMBD with MA in children aged 6 months to 12 years [11].…”
Section: Introductionmentioning
confidence: 99%